Aplikasi Pemesanan Makeup Artist Berbasis Mobile Pada Anida Makeup - Anida Hasna Nur Fadhila; Tri Haryanti; Purwanto . (CV. ITTC INDONESIA, 2025)
The Makeup service industry is growing in line with increasing customer demand for practical and fast services. However, at Anida Makeup, the ordering process is still manual, with PDF price lists sent via private message, making it inefficient and making it difficult to update information. This study aims to develop a mobile-based Makeup artist ordering application that can facilitate customers in obtaining service information and placing orders directly. The research method uses a qualitative and quantitative approach (Mixed Methods). Qualitative data collection includes observation, interviews, documentation, and literature studies as the primary data collection method. The quantitative approach focuses solely on questionnaire data collection using a Likert scale. The application was developed using a prototyping model with stages of needs analysis, design using Unified Modeling Language (UML), implementation using Flutter, Dart, and MySQL, and supported by XAMPP and Visual Studio Code software. Testing was conducted using blackbox and questionnaires. The test results showed an average score of 90% from customers and 90% from administrators. This indicates that the system is capable of improving the efficiency of the Makeup ordering process for users. Furthermore, the system also helps business owners improve operational efficiency and manage order data in a more structured manner.